Increased angiotensin II from adipose tissue modulates myocardial collagen I and III in obese rats - da Silva-Bertani, Danielle Cristina Tomaz [UNESP]; Vileigas, Danielle Fernandes [UNESP]; Mota, Gustavo Augusto Ferreira [UNESP]; de Souza, Sérgio Luiz Borges [UNESP]; Sant'Ana, Paula Grippa [UNESP]; Freire, Paula Paccielli [UNESP]; de Tomasi, Loreta Casquel [UNESP]; Corrêa, Camila Renata [UNESP]; Padovani, Carlos Roberto [UNESP]; Fernandes, Tiago; de Oliveira, Edilamar Menezes; Cicogna, Antonio Carlos [UNESP] (Elsevier, 2020)
It has been described that the cardiac dysfunction in the obesity model is because of collagen imbalance and that angiotensin II (Ang II) contributes to myocardial fibrosis. However, it remains undefined if changes in collagen I and III metabolism in obesity is due to the renin-angiotensin system (RAS) dysregulation from myocardium or excessive adipose tissue. Aim: This study aimed to verify whether the changes in myocardial collagen metabolism result from RAS deregulation of cardiac or adipose tissue in an obesity model. Main methods: Wistar rats were fed with control (CD) and high-fat (HFD) diets for 30 weeks. After the dietary intervention, animals were assigned to be treated with losartan at the 30 mg/kg/day dosage or kept untreated for an additional five weeks. Key findings: HFD induced obesity, comorbidities, and cardiac collagen overexpression. The HFD group presented an increase in Ang II levels in both adipose tissue and plasma, as well as AT1 receptor expression in cardiac tissue. Of note, the myocardial Ang II was not changed in the HFD group. Losartan administration reduced some obesity-induced comorbidities regardless of weight loss. The AT1 receptor blockade also decreased the release of Ang II from adipose tissue and myocardial AT1 receptor and collagen. Significance: It was seen that excessive adipose tissue is responsible for the exacerbated circulating Ang II, which induced cardiac fibrosis development.
Keywords: Collagen; Heart; High-fat diet; Losartan; Obesity; Renin-angiotensin system